Spontaneous regression of cerebral arteriovenous malformation- Case report - Jha, Rajiv; Jha, Prabhat (Nepal Journal of Neuroscience, 2022)
Spontaneous regression of cerebral arteriovenous malformation is rare and less than hundred cases have been reported in literature. The authors report a case of 64 year/male who was diagnosed with cerebral arteriovenous malformation which was found to undergo spontaneous regression on repeat imaging. Spontaneous regression of a cerebral arteriovenous malformation is a rare phenomenon.